Analysis of Expressive Utterances on Social Media of BBM Update Statuses - Agus Muharyanto (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2018)
This research aims to describe the linguistic form of expressive utterancesand describe the intentions of expressive utterance in status updates on social media Blackberry Messanger (BBM) used by students of STKIP PGRI Tulungagung. It is descriptive qualitative research which the writer uses documentation and observation method as the method of collecting data. The type of this research is descriptive qualitative research which the writer uses documentation and observation method as the method of collecting data. There are 20 data of expressive utterance. There are seven kinds of expressive utterance from fifty data found in status update BBM. They are word, verb phrase, adjective phrase, noun phrase, declarative sentence, impertive sentence, and exclamatory sentence. The types of expressive utterance found in status update on BBM dominated by declarative sentence. The intention of expressive utterance are yearning, anger expression, welcoming, congratulating, tiredness, hoping, happiness, love,Â  thanking, sadness, sorrow, worrying, like, dislike, apologizing, pleasure, shock, and longing.